G310(P) Improving the quality of information sharing in child safeguarding. (27th April 2016) - Sturrock, S; Wong, YL; Mahoney, R; Kashora, F; Ioannou, Y
Abstract : Aims: Safeguarding is a core aspect of paediatric practice to protect children from maltreatment in the community and in hospital. General Practitioners (GPs) are pivotal to coordination of care and response to safeguarding issues, and it is vital that relevant information is shared clearly and effectively between the hospital and GPs. Our aim was to assess and improve the quality of information recorded in discharge summaries in children with new or pre-existing safeguarding concerns. Methods: Children with new or existing safeguarding concerns presenting to a London tertiary hospital are recorded in a database. One hundred presentations were identified over twelve months. Summaries were assessed using a proforma developed from local and national guidelines. Interventions to improve DSUMs recording were assessed for their impact after each cycle (Figure 1 ). Results: Figure 2 summaries the results of the three cycles. Safeguarding concerns were reported in 60%, 40% and 35% respectively, and specific concerns similarly detailed in 40%, 55% and 32% of discharge summaries. Following the second cycle, further training and a checklist using the acronym 'SAFER' was implemented (Figure 3 ). A survey of GPs was conducted confirming key information they required in summaries. Social worker involvement was mentioned in 43% for the first two cycles and 36% in the final cycle. The IT system at the hospital is currently being modified to prompt doctors to include all relevant information. Conclusions: There were inconsistencies in reporting of all relevant and appropriate information relating to child safeguarding concerns. Possible barriers include anxiety about recording sensitive information, non-paediatric specialities recording only specialty specific information such as operation details and trainees completing summaries not directly involved in care of the child, due to shifts. Interventions have not consistently changed practice; therefore an electronic solution has been developed to include mandatory prompts for relevant and appropriate safeguarding information. The electronic solution has been approved for introduction, and will be developed and evaluated. While this intervention may improve quality of reporting, senior supervision remains vital in monitoring the quality of the information that is essential for successful multidisciplinary and multiagency working to safeguard children.